Acetylcholine, melatonin, and potassium depolarization stimulate release of luteinizing hormone-releasing hormone from rat hypothalamus in vitro. - Richardson, S B (1982)
We have examined the release of radioimmunoassayable luteinizing hormone-releasing hormone (LH-RH) from fragments of rat medial basal hypothalamus. These fragments were cultured overnight in medium containing serum and then preincubated in groups of three for 10 min in medium resembling cerebrospinal fluid in its electrolyte constituents and containing bacitracin. This was followed by 30-min incubation periods during which some of the hypothalami were exposed to test substances. Potassium depolarization, effected by the addition of 56 mM potassium chloride to the incubation medium, caused a marked stimulation in LH-RH release, but only in the presence of calcium. Acetylcholine at 10 nM and the parasympathomimetic anticholinesterase agent neostigmine at 1 microM markedly stimulated LH-RH release. Hexamethonium, a nicotinic antagonist, at 1 microM abolished the acetylcholine-induced increment in LH-RH release. Melatonin, a pineal indolamine, caused significant stimulation of LH-RH release at a concentration as low as 10 nM. Bacitracin (21 microM) was employed in all these experiments. It had no effect on LH-RH release but did prevent the degradation of LH-RH in this system. We conclude that acetylcholine and melatonin are capable of inducing LH-RH release from the rat medial basal hypothalamus. These actions may account for some of the progonadotropic properties previously ascribed to these agents.